Pendampingan Keterampilan Tentang Kompetensi Ijtihad Dalam Aspek Ilmu Mawaqit Ilmu Falak Pada Pondok Pesantren Di Kabupaten Sumedang - Zulbaidah Zulbaidah; Didah Durrotun Naafisah (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
When discussing mawaqit in pesantren, it becomes clear that not all pesantren implement theory and practice in the same manner. One of these practices is when it's time for prayer. Astronomy is the idea of using arithmetic to calculate things within various Islamic rules. The purpose of this service is to use mentoring to help the community in Sumedang Regency better understand ijtihad and astronomy. The method used is qualitative, where the service provider is the main tool, sample, and data source. The results focus on meaning rather than generalization. The results of this investigation reveal that determining the direction of the Qibla mathematically is difficult in some places. Spherical astronomy and geography are the main issues with prayer direction. There are two ways to determine when the month in the Islamic calendar begins: the calculation method and the observation method. To know the time of Imsak, you also need to know the time of the Subuh prayer. Muslims often miscalculate the time of the Subuh prayer when trying to determine it. Some rules regarding the height of the sun were made by experts through ijtihad. The Ministry of Religious Affairs uses this ijtihad to determine when dawn begins, when true dawn light is visible on the eastern horizon before sunrise, and when the sun is below the eastern horizon until it is visible.